Intimate partner violence during lockdown in Tuscany, Italy: economic shock or confinement-related stressors? - Francesca Bettio; Fernando Flores Tavares; Elisa Ticci (Global Labor Organization (GLO), 2024)
We revisit the issue of Intimate Partner Violence (IPV) during the COVID-19 pandemic asking three questions: whether IPV increased with lockdown, what pandemic-specific 'shocks' or 'stressors' had the greatest impact and how the results change when different measures of IPV are used. Leveraging a large telephone survey conducted in 2021 in the Italian region of Tuscany as part of a mixed-method research project on IPV during the first lockdowns, we show that IPV intensified. As regards pandemic-specific shocks or stressors, we find that parental overburden due to the presence of minors had the largest impact, followed by job loss, whereas confinement to crowded spaces lacking privacy appeared to have a weak effect, if any. Finally, and unsurprisingly, we find that using a fuzzy measure of violence outcomes that accounts for severity as well as prevalence of violence modifies the findings in important respects. In particular, job loss appeared to trigger less severe abuse than parental overburden. Our empirical strategy principally relies on the exogeneity of pandemic-specific shocks to attribute causal interpretation to our estimates. However, our dependent variables (IPV outcomes) are binary or fractional, and endogeneity cannot be ruled out. To address these aspects, we estimate average marginal effects using a two-step Control function (CF) approach combined with a quasilikelihood method.
Keywords: C49; D63; J16; 330; Intimate partner violence; COVID-19 pandemic; Fuzzy set theory; Control-function method; Italy; Gender